Percepções frente ao risco de deslizamento - Rafaela Vieira; Sandra Maria de Arruda Furtado (Geosul, 2005)
Landslides are frequent in Blumenau. They are influenced by the physical characteristics of the landscape and given greater potential by the social structure. Given that the state has taken few actions to avoid landslides, the community is limited to structural and individual measures. Those of a collective nature are discussed but not executed. Taking the risk of living in regions of landslides has been the solution found to having a place to live, which combined with social relations are important in the identification of place.